Whose Paper Is It Anyway? Authorship Criteria According to Established Scholars in Health Professions Education. (August 2018) - Uijtdehaage, Sebastian; Mavis, Brian; Durning, Steven J.
Abstract : Purpose: The health professions education (HPE) community is a crossroad of scholars from various disciplines with potentially conflicting views on who qualifies as author. Established HPE scholars are expected to model ethical research conduct, but no research has investigated the extent to which authorship criteria are understood and applied by leaders in the field. This study investigated what leading scholars consider appropriate criteria for authorship and how often these criteria are ignored. Method: Directors of research and editors of HPE journals completed an anonymous survey between September 2015 and August 2016 with questions about authorship practices they experienced and recommended, common authorship criteria, and how often they had encountered unethical authorship decisions. Results: Out of 82 invited scholars, 46 participated in the survey (response rate = 56.0%). They reported a stark contrast between current and recommended authorship practices. Twenty-two (51.2%) had experienced unethical pressure regarding authorship order, 15 (34.9%) had not been included as author when they qualified, and 25 (58.1%) had seen authors included who did not qualify. A slight majority (n = 25; 58.1%) correctly identified authorship standards widely adopted by biomedical journals. Conclusions: A surprising proportion of leaders in the HPE field had encountered unethical authorship practices. Despite widely disseminated authorship criteria, the findings suggest that offering authorship to those who do not qualify, or arguably worse, excluding those who should have been included, remains a common practice. The authors offer strategies to scholars, editors, and tenure and promotion committees to combat these practices. Abstract : Supplemental Digital Content is available in the text.